PENDIDIKAN MULTIKULTUR: MEMBANGUN KEBERAGAMAN INKLUSIF DAN MODERAT DI KALIMANTAN BARAT - Eka Jaya (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2013)
Multicultural education may be one strategy to introduce the local culture to the learner so that an understanding of cultural diversity to be more thorough and complete. West Kalimantan is an area that is very sensitive to the ethnic conflict, the issue of cultural differences generated by different ethnic interests was used as a tool to exacerbate that conflict often occurs in West Kalimantan. Looking at the situation that the approach by leveraging cultural diversity can inclusivity views of learners and learning with the modernization of systems and contextual environment. So that conflicts can be mitigated through education, of course, the role of teachers and lecturers are also key to the success.